BDNF rs10501087, rs1491850 and rs11030094 polymorphisms associated with delayed progression in early-stage Parkinson's disease - Fischer, D. Luke; Auinger, Peggy; Goudreau, John L.; Paumier, Katrina L.; Cole-Strauss, Allyson; Kemp, Christopher J.; Lipton, Jack W.; Sortwell, Caryl E. (Frontiers in Neurology, 2022)
Parkinson’s disease (PD) is heterogenous in its presentation, progression and response to therapies. Genetic polymorphisms may account for some of this variability. Several single nucleotide polymorphisms (SNPs) in the brain-derived neurotrophic factor gene BDNF have been associated with differing clinical outcomes from different dopaminergic replacement strategies, and one of these, the rs6265 SNP, has been associated with a milder clinical phenotype in the unmedicated, early-stage of PD. We examined if other BDNF SNPs with potential pharmacogenetic effects also are associated with different rates of disease progression. The Deprenyl And Tocopherol Antioxidative Therapy Of Parkinsonism (DATATOP) study was analyzed retrospectively. DNA samples (n = 217) were genotyped for the BDNF rs908867, rs11030094, rs10501087, rs1157659 and rs1491850 SNPs, and the primary endpoint was time to initiate symptomatic pharmacotherapy. Genotypes were compared using the Cox proportional hazard ratio (HR) with baseline age, sex, site, time since PD diagnosis and rs6265 genotype as covariates. The primary endpoint was associated with a delay with three SNPs: rs10501087 (HR (95% Confidence Interval)=28.3 (3.6-223.1, p=0.002) and 7.6 (1.9-29.8, p=0.004) for T/T and T/C subjects, respectively, vs. C/C subjects), rs1491850 (HR=3.3 (1.3-8.4, p=0.04) and 2.8 (1.3-6.4, p=0.03) for T/T and T/C subjects, respectively, vs. C/C subjects) and rs11030094 (HR=2.5 (1.1-5.6, p=0.03) and 2.0 (1.3-6.4, p=0.03) for A/A and A/G subjects, respectively, vs. G/G subjects). From the primary endpoint, specific rs10501087, rs1491850 and rs11030094 SNP genotypes are associated with a slower rate of PD progression in the unmedicated state. A prospective clinical trial examining many BDNF SNPs is warranted.